Disjoint components of manifest time: Commentary: Physical time within human time - Arstila Valtteri (FRONTIERS MEDIA SA, 2025)
A Commentary on
Physical time within human time
Gruber, R. P., Block, R. A., and Montemayor, C. (2022). Front. Psychol. 13. doi: 10.3389/fpsyg.2022.718505